Cytochalasin B Modulates Nanomechanical Patterning and Fate in Human Adipose-Derived Stem Cells - Eva Bianconi; Riccardo Tassinari; Andrea Alessandrini; Gregorio Ragazzini; Claudia Cavallini; Provvidenza Maria Abruzzo; Giovannamaria Petrocelli; Luca Pampanella; Raffaella Casadei; Margherita Maioli; Silvia Canaider; Federica Facchin; et al. (Cells, 2022)
Cytoskeletal proteins provide architectural and signaling cues within cells. They are able to reorganize themselves in response to mechanical forces, converting the stimuli received into specific cellular responses. Thus, the cytoskeleton influences cell shape, proliferation, and even differentiation. In particular, the cytoskeleton affects the fate of mesenchymal stem cells (MSCs), which are highly attractive candidates for cell therapy approaches due to their capacity for self-renewal and multi-lineage differentiation. Cytochalasin B (CB), a cyto-permeable mycotoxin, is able to inhibit the formation of actin microfilaments, resulting in direct effects on cell biological properties. Here, we investigated for the first time the effects of different concentrations of CB (0.1–10 μM) on human adipose-derived stem cells (hASCs) both after 24 h (h) of CB treatment and 24 h after CB wash-out. CB influenced the metabolism, proliferation, and morphology of hASCs in a dose-dependent manner, in association with progressive disorganization of actin microfilaments. Furthermore, the removal of CB highlighted the ability of cells to restore their cytoskeletal organization. Finally, atomic force microscopy (AFM) revealed that cytoskeletal changes induced by CB modulated the viscoelastic properties of hASCs, influencing their stiffness and viscosity, thereby affecting adipogenic fate.